Innovative Teaching and Technology Integration: Exploring Elderly Teachers’ Attitudes - Bazila Tariq (International Islamic University Islamabad, 2020)
To stay current in this dynamic age, innovation and adaptability is not only considered a key to success, rather it is deemed a significant tool of survival. The field of education has metamorphosed with the shift of focus from teachers’ teaching to students’ learning. This change implies that teachers consistently update their practices and innovate in order to meet the needs of students with diverse skills. With the introduction of student-centred classrooms, project based learning, practical discovery and technological integration, the traditional lecture methods and the idea of passive students is becoming obsolete. However, the attitude of teachers towards innovation varies. The aim of this study was to explore attitudes of elderly teachers towards innovative teaching strategies. This study used qualitative phenomenological study method and criterion sampling technique to select four participants aged 45 years and above. Data were gathered through a self-constructed semi structured interview guide containing three dimensions. Phenomenological data analysis of these three dimensions showed the presence of some cognitive, behavioural and affective resistance to change among teachers. Therefore, it is suggested that certain aspects of training and guidance need to be provided to elderly teachers in order to make the process of innovation easy to adopt.